2001
DOI: 10.1152/ajpregu.2001.280.6.r1887
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of basal metabolism from organ size in the rat: relationship to strain, feeding, age, and obesity

Abstract: Use of the weight of various organs and tissues together with their specific metabolic activity for prediction of basal metabolism (BM) seems to be promising. In this study we compared the use of this method with those based on simple or multiple regression analyses. We observed that 97.4% of differences in BM in a group of nine adult male Wistar rats weighing 273--517 g could be accounted for by changes in tissue and organ weights. BM measured in lean Zucker and Sprague-Dawley rats did not diverge from the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 50 publications
(35 reference statements)
2
57
1
Order By: Relevance
“…64% of lean body mass and ca. 45% of BM (Even et al 2001); this is consistent with ash-free, fat-free carcass mass (an approximation of total skeletal muscle mass) in mice of ca. 44% of BM (Corva and Medrano 2000).…”
Section: Appendix: Total Carbohydrate In a Mousesupporting
confidence: 77%
See 2 more Smart Citations
“…64% of lean body mass and ca. 45% of BM (Even et al 2001); this is consistent with ash-free, fat-free carcass mass (an approximation of total skeletal muscle mass) in mice of ca. 44% of BM (Corva and Medrano 2000).…”
Section: Appendix: Total Carbohydrate In a Mousesupporting
confidence: 77%
“…Mammalian body stores of carbohydrate-glycogen in liver and muscle-are quite limited, and account for only 200-500 g total in humans (Flatt 1995) and ca. 0.65% of fat-free mass in rats (Even et al 2001;Morifuji et al 2005). Since glucose is an essential substrate for the cat, the question is how this demand can be met on a hypercarnivorous diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the mechanistic level, it is suggested that BMR declines with age because the mass of metabolically active tissue as well as their mass-specific metabolic activity declines with age (e.g. Even et al 2001;Roberts & Rosenberg 2006). The latter is also supported by the finding that tissue of aged rats shows a decreased capacity to produce ATP by oxidative phosphorylation ( Navarro & Boveris 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Basal metabolic rate (BMR) or resting metabolic rate declines with age in humans (Roberts & Rosenberg 2006) as well as in rats (e.g. Even et al 2001), dogs (Speakman et al 2003) and some species of birds (Broggi et al 2007). However, other studies on birds, naked mole rats and mice did not report any age-related decline in BMR (see references in Moe et al 2007).…”
Section: Introductionmentioning
confidence: 99%